Semantic prerequisites for data sharing in a biomedical research network - Ganzinger, Matthias; Knaup-Gregori, Petra (Medinfo 2013, 2013)
We investigated for a research network on liver cancer semantic prerequisites for successful data sharing. To support collaboration with information technology, it is important to annotate research data with metadata. Ideally, all data handled are described ontologically to allow for automated reasoning. However, a complete ontology is hard to define. As a preliminary step we acquired a project wide common vocabulary by interviewing project partners. The vocabulary contains terms for describing the projects' processes and related data. Where the vocabulary intersects with Unified Medical Language System (UMLS) terms, the terms will be replaced by UMLS-terms. Cell line data are a subclass of the data handled in our research network. For these data we reviewed existing ontologies and developed a new ontology for cell lines. The Cell Culture Ontology (CCONT) reuses existing ontologies and enhances those with more specific cell line related properties to achieve a comprehensive description of cell lines. The results of our work can be transferred to other research networks with a similarly limited biomedical scope.